On the Stereochemical Course of Asymmetric Mannich Reactions - Dieter Seebach; Martin Schiess; W. Bernd Schweizer (CHIMIA)
In the TiCl4-mediated Mannich reaction, β-amino ketones are obtained with diastereoselectivities of 70-95%. The configuration of the major isomer obtained from benzaldehyde, piperidine, and cyclohexanone [2-(α-piperidinobenzyl)cyclohexanone 1] is shown by X-ray crystallography to be unlike (u, cf. Fig. 1). Thus, the trigonal centers combine to form the C–C bond with relative topicity like (lk, 3). Possible mechanisms of  the reaction are briefly discussed.